Overview of knowledge, attitudes and behavior of housewives in Denpasar City towards self-medication - Ruspita Sari, Ni Ketut Adelia; Kasih Permatananda, Pande Ayu Naya; Cahyawati, Putu Nita; Aryastuti, Sri Agung; Lestarini, Asri (Science Midwifery, 2025)
Self-medication is an effort to prevent and treat diseases without consulting a doctor, with housewives as the main actors. Factors that influence self-medication are knowledge, attitudes, and behavior. This study aims to determine the level of knowledge, attitudes, and behavior of housewives in Denpasar towards self-medication. The method used is descriptive observational with a cross-sectional approach. Respondents numbered 100 people who were selected based on inclusion and exclusion criteria. Data were collected through questionnaires and analyzed in the form of a frequency distribution table. The majority of respondents were 26-35 years old (60%), had a college/diploma education (68%), and worked as private employees (39%). The most frequently used medicine was cough and cold medicine (37%). The results showed that 67% of respondents had high knowledge, 58% had a positive attitude, and 92% had good behavior in self-medication. It is hoped that the results of this study will encourage rational self-medication practices, with the support of the government and health institutions in comprehensive education programs, including drug classification. The government and related agencies, including health education institutions, are trying to strengthen self-medication knowledge improvement programs, which not only focus on DAGUSIBU (can, use, store, dispose), but also drug classification and others.